Lacosamide as the first add-on therapy in adult patients with focal epilepsy: A multicenter real-world study - Liu, Wenyu; Li, Wenjing; Wang, Peiyu; Zhang, Hesheng; Zhang, Enhui; Wu, Xintong; Zhou, Dong (Frontiers in Neurology, 2023)
Background: Prospective observations on the effectiveness, safety, tolerance, and the influence of comorbidity of add-on LCM therapy are still lacking, especially for domestic generic LCM in China. Objective: In this multicenter, real-world study, we aimed to evaluate lacosamide (LCM) as first add-on therapy in adult Chinese patients with focal epilepsy that had initially been treated with monotherapy. Methods: A cohort of consecutive focal epilepsy patients aged over 16 years were enrolled and followed at the multi-epilepsy centers in China. LCM was prescribed as the first add-on therapy. The main outcome measures included seizure frequency and response rate. Data of seizure-free rate, retention rate, scales of depression and anxiety, and adverse events were also collected as additional outcome measures. Results: A total number of 107 adult subjects (60 males, 56.07%) were enrolled. The mean age was 37.16 ± 15.01 years, and the mean age at seizure onset was 312.35 ± 199.97 months. After the LCM add-on therapy, the ≥50% response rates were 76.19%, 81.73%, 94.12%, 95.79% at the visit at 4 weeks (visit 2), 8 weeks (visit 3), 16 weeks (visit 4), and 24 weeks (visit 5), respectively, compared to baseline (visit 1). Thirty-four patients (31.78%) had no seizures during the whole follow-up period. The post-treatment emotional performance of the 97 subjects, defined as generalized anxiety disorder (GAD) and Neurological Disorders Depression Inventory (NDDI) scores, was significantly better than the baseline one. Only one patient suffered from mild dizziness. Conclusions: LCM as first add-on therapy in adult focal epilepsy in China was effective and safe. Further prospective studies with long-term follow-up periods are needed to confirm our present findings. Clinical Trials.gov Registration: ChiCTR2100042485